The internationalization of Petrobras in Bolivia: the challenges of a plurinational state - Baptista, Renato Dias [UNESP]; Santini Pigatto, Giuliana Aparecida [UNESP] (Pontificia Univ Catolica Sao Paulo-puc-sp, 2015)
The Brazilian organizations has expanded its productive internationalization process in recent decades. Among the numerous actions for the success of this expansion, the local culture is an essential element to be studied and incorporated into the organizational learning. Petrobras, petroleo, brasiteiro SA is in the list of Brazilian transnational corporations that accumulate experience about the values rooted in the different countries where they realize direct investments. The objective of the research was to analyze the Interfaces of local culture in the Bolivian unit of Petrobras. The methodological procedures used were the bibliographical and documentary research. The data showed the forces of the culture in a territory where permeated political tensions that; concomitantly, required knowledge to manage the business in a rnulteultural society.
Keywords: Internationalization; Culture; Petrobras-Bolivia